Students' Conceptions About Flat Side Space Materials Viewed From The Cognitive Styles of Students in Junior High School - Hardi, Novan; Tambo, Isaac Daniel; Fabelurin, Olanrewaju; Khaminsou, Bounmy (Interval: Indonesian Journal of Mathematical Education, 2023)
This research is a qualitative research using a case study research design. The subjects in this study were students of class VIII even semester at SMP Negeri 2 Bayan which consisted of one class. The interview guideline instrument was in the form of a question guide used by researchers to gather information on students' conceptions of: (1) the definition of cubes and blocks and (2) the elements of cubes and blocks. Qualitative data analysis is carried out interactively and continues continuously until complete, so that the data is saturated. Data analysis techniques in this study used the Miles and Huberman methods. The results of this study are the conception of class VIII students of SMP Negeri 2 Bayan who have a field dependent (FD) Cognitive Style in stating the definition of cubes and blocks by stating that cubes are geometric shapes that have the same sides and blocks are geometric shapes that have unequal sides, by declaring that a cube is a geometric shape that has 6 square sides while a beam is a geometric shape formed from a combination of squares and rectangles, by stating that a cube is a figure whose sides are the same while a block is a figure that has length , width, and height.